(untitled) (Modern American Journal of Linguistics, Education, and Pedagogy, 2026)
This article thoroughly analyzes the positive and negative impacts of media influence on the upbringing of primary school students. It also develops recommendations for parents and educators on how to properly guide children’s interaction with media. The findings underscore the critical importance of media literacy in ensuring the healthy development of children.